Efficacy of scintigraphy as a diagnostic aid in oral and maxillofacial pathologies: A comparative radionuclide-radiographic study - Ankur Singh; Nitin Agarwal; Kamala Rawson; Basavaraj N Kallalli; Abhishek Sinha; Yatriben Sandesara (Wolters Kluwer Medknow Publications, 2015)
Aims and Objectives: The aim of this study was to investigate various lesions involving the oral and maxillofacial region by using scintigraphy and to compare the findings with those of conventional radiograph. Materials and Methods: Nineteen subjects of all age groups and both sexes who reported to the outpatient department of Oral Medicine and Radiology and had been clinically diagnosed with diseases of oral and maxillofacial region were selected. Conventional radiography and scintigraphy were performed for all the subjects. Biopsy and histopathological investigations were preformed to confirm the diagnosis and on the basis of which sensitivity, specificity, positive predictive value, and efficiency of conventional radiography and scintigraphy were evaluated. Results: Conventional radiography was found to have 94.11% sensitivity, 50% specificity, 94.11% positive predictive value, and 89.47% efficiency. Scintigraphy was found to have 100% sensitivity, 14.28% specificity, 66.66% positive predictive value, and 68.42% efficiency. Conclusion: Scintigraphy is a very sensitive diagnostic aid, but lacks in specificity. Conventional radiography, on the other hand, has good sensitivity and relatively better specificity. For a proper diagnosis, scintigraphic findings must be correlated with clinical, radiological, and histopathological findings.